Polar vortex and generation fuel diversity - Hayat, Hassan (Kansas State University, 2015)
The unusual weather events during the polar vortex of 2014 illuminated the needs for fuel diversity for power generation in order to allow reliable operation of the electricity grid. A system wide reliability assessment for winter months should be undertaken in addition to the summer months to ensure reliable operation of the electricity grid throughout the year. Severe weather conditions that lead to equipment malfunction during the polar vortex should be thoroughly investigated and remediations to ensure satisfactory future performance of the grid must be undertaken. Environmentally unfriendly emissions from power plants must be minimized but diversity of generation fuel must be maintained. Future energy policies must be formulated with consideration that approximately 14 GW of coal generation in Pennsylvania Jersey Maryland Regional Transmission Organization’s control area available during the polar vortex will be retired by 2015 and replaced with plants that utilize fuel types other than coal.
Keywords: Coal generation retirement; Electric grid; NERC transmission grid planning standards; Power generation fuel diversity; Polar vortex; Electrical Engineering (0544)